Modes of Media: - Nazah Farhat (Crossings, 2021)
The objective of this paper is to discuss the features and functions of the semiotic resources used in Bangladeshi television reports. Although the verbal mode is usually considered one of the primary modes of communication, all communication is essentially multimodal in nature. Television news reports are a combination of such multiple styles, for they deliver a meaning by integrating various linguistic and non-linguistic modes. Linguistic modes such as words, sounds, sentences, and so on are used in the speech of the report. On the other hand, non-linguistic modes such as moving images, background music, colors, and elements alike are chosen to complement the linguistic modes. Therefore, it is important to investigate how these modes are combined and the role they play in the process of meaning-making. This research analyzes three Bangladeshi television news reports using Michael Halliday’s theoretical framework of metafunctions to understand how these multiple modes are combined to make complete meaning. From this research, it is evident that the linguistic and non-linguistic modes used in television reports require a careful selection to be aligned with the professional variety of broadcast journalism.